Pharmacological interactions between phenylbenzothiazoles and aryl hydrocarbon receptor (AhR) - Bazzi, Rana (2008)
The aryl hydrocarbon receptor is a ligand-dependent transcription factor that induces expression of a number of genes encoding drug metabolizing enzymes, such as CYP1A1, CYP1A2 and CYP1B1. Recently, it was suggested that the AhR signaling pathway may be involved in mediating the anticancer activity of novel 2-(4-aminophenyl) benzothiazole drugs in MCF-7 breast cancer cells. There is no direct proof of direct binding between these drugs and AhR, and it is also unclear how AhR signaling per se plays a role in the activity of these drugs. This study investigates the role of AhR in the mechanism of action of the benzothiazole drugs by determining the ability of these drugs to bind to the rat hepatic AhR, to induce CYP1A1 mRNA and to inhibit cell growth in rat hepatoma H4-II-E cells.